Immunometabolism – The Role of Branched-Chain Amino Acids - Yahsi, Berkay; Gunaydin, Gurcan (Frontiers in Immunology, 2022)
Immunometabolism has been the focus of extensive research over the last years, especially in terms of augmenting anti-tumor immune responses. Regulatory T cells (Tregs) are a subset of CD4+ T cells, which have been known for their immunosuppressive roles in various conditions including anti-tumor immune responses. Even though several studies aimed to target Tregs in the tumor microenvironment (TME), such approaches generally result in the inhibition of the Tregs non-specifically, which may cause immunopathologies such as autoimmunity. Therefore, specifically targeting the Tregs in the TME would be vital in terms of achieving a successful and specific treatment. Recently, an association between Tregs and isoleucine, which represents one type of branched-chain amino acids (BCAAs), has been demonstrated. The presence of isoleucine seems to affect majorly Tregs, rather than conventional T cells. Considering the fact that Tregs bear several distinct metabolic features in the TME, targeting their immunometabolic pathways may be a rational approach. In this Review, we provide a general overview on the potential distinct metabolic features of T cells, especially focusing on BCAAs in Tregs as well as in their subtypes.